Cognitive impairment in adolescent and young adult cancer patients: Pre‐treatment findings of a longitudinal study. (11th October 2022) - Chan, Alexandre; Cheng, Ivy; Wang, Claire; Tan, Chia Jie; Toh, Yi Long; Ng, Ding Quan; Koh, Yong Qin; Zhou, Hanzhang; Foo, Koon Mian; Chan, Raymond Javan; Ho, Han Kiat; Chew, Lita; et al.
Abstract: Background: There is little information about cancer‐related cognitive impairment (CRCI) in adolescent and young adults (AYA, 15–39 years old) due to its rare incidence. Here, we present the pre‐treatment (before chemotherapy or radiotherapy) evaluation of cognitive function and ability of AYA with cancer (AYAC) in a multicentered cohort study. Methods: Newly diagnosed AYAC and age‐matched healthy controls (HC) were recruited between 2018 and 2021. The primary outcome was the comparison of pre‐treatment cognitive impairment defined as 2 standard deviations (SDs) below the HC on ≥1 cognitive test, or >1.5 SDs below on ≥2 tests using CANTAB® between AYAC and HC. Secondary outcomes included self‐perceived cognitive ability assessed by FACT‐Cog v3 and biomarkers (inflammatory cytokines and brain‐derived neurotrophic factor [BDNF]). Results: We recruited 74 AYAC (median age = 34) and 118 HC (median age = 32). On objective cognitive testing, we observed three times more AYAC patients performed poorly on at least 2 cognitive tests compared to HC (40.5% vs. 13.6%, p < 0.001). AYAC self‐perceived less degree of cognitive impairment than HC ( p < 0.001). However, AYAC perceived a greater impact of cognitive changes on their quality of life compared to HC ( p = 0.039). Elevated baseline inflammatory markers (IL‐2, IL‐4, IL‐6, IL‐8, IL‐10 and IFN‐γ) were observed among AYAC compared to HC, and baseline BDNF was lower in AYAC compared to HC. Interaction effects between cancer diagnosis and biomarkers were observed in predicting cognitive function. Conclusion: With the pre‐existence of CRCI and risk factors of neuroinflammation even prior to systemic therapy, AYAC should receive early rehabilitation to prevent further deterioration of cognitive function after initiation of systemic therapies. (ClinicalTrials.gov Identifier: NCT03476070). Abstract : This study reported about pre‐treatment cancer‐related cognitive impairment between newly diagnosed AYAC and age‐matched healthy control. There were higher proportions of subjects with impairment and elevated inflammatory marker levels among AYAC compared to controls. At the same time, lower levels of self‐perceived impairment and lower baseline BDNF levels were reported in this patient group.